Ukuran Perusahaan, Leverage, Profitabilitas, dan Agresivitas Pajak - Krisna, I Gede Putu Aditya Paramananda; Supadmi, Ni Luh (E-Jurnal Akuntansi, 2023)
Tax aggressiveness is a concept to reduce the tax burden through tax planning that can be implemented through tax avoidance or tax evasion. The research objective is to prove the effect of company size, leverage, and profitability on tax aggressiveness as calculated by the effective tax rate proxy. The population in this study were all LQ45 index companies listed on the Indonesia Stock Exchange totaling 45 companies. The method of determining the sample using purposive sampling method and obtained 54 observations. The sample in the study amounted to 54 observational data or observations consisting of 18 companies which included a sample determination qualification with an observation period of three years. The data analysis technique used in this research is multiple linear regression. The results of the study found that firm size, leverage, profitability have a positive effect on tax aggressiveness. That is, the larger the size of the company, increased leverage and profitability, the higher the tax aggressiveness that is implemented. Keywords: Tax Aggressiveness, Leverage, Profitability, Company Size